2018
DOI: 10.1590/1677-5449.170111
|View full text |Cite
|
Sign up to set email alerts
|

Balões de látex: um modelo alternativo e de baixo custo para treinamento de anastomoses vasculares no ensino médico

Abstract: Resumo O uso de simuladores na educação médica tem sido cada vez mais frequente, porém pouco acessíveis devido ao custo elevado. Foi desenvolvido para tal um modelo acessível e de baixo custo para o aprendizado e o treinamento de suturas e anastomoses vasculares em Laboratório de Bases das Técnicas Cirúrgicas. Foram utilizados balões de látex de cores variadas, fio de polipropileno 6.0 e outros materiais específicos para sutura vascular (porta-agulhas e pinças). Para facilitar o reparo dos balões, eles foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Use of latex balloons for training vascular anastomoses was described by Sarmento et al, 15 who reported that their malleability, cylindrical shape, thinness, and internal lumen were all similar to blood vessels. In that model, the balloons were not filled with any intraluminal contents, in contrast with the present study, in which gelatin was used, so that the balloons would remain turgid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of latex balloons for training vascular anastomoses was described by Sarmento et al, 15 who reported that their malleability, cylindrical shape, thinness, and internal lumen were all similar to blood vessels. In that model, the balloons were not filled with any intraluminal contents, in contrast with the present study, in which gelatin was used, so that the balloons would remain turgid.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of low-cost models of vascular anastomosis, one limitation is related to evaluating the quality of the distance between stitches, since in these synthetic models there are no coagulation factors to reduce leakage between stitches. 1,15 Even though spacing of approximately 1 mm between stitches was maintained, discrete leakage of gelatin was observed, which was expected because of the physical characteristics of the material. However, the peculiar expansivity of the gelatin also made it possible to attest to the patency of anastomoses, since once the clamps had been removed, the gelatin moves to fill the space; other models depend on intraluminal injection of liquid to test the patency of anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the student participants were given practical and individual instruction by an experienced vascular surgery professor, based on a demonstration of performing an end-to-side anastomosis using the technique recommended by Rutherford, 16 with initial sutures at the angles and closure of the anterior and posterior walls with continuous sutures. 16,17 The endto-side anastomosis was performed on the alternative low cost training model, constructed with a wooden board, screws, and latex balloons 15 (Figure 1), and a surgical materials kit containing four straight forceps for sutures, two needle holders, one pair of scissors, and 5-0 polypropylene suture material, which were used to conduct the vascular anastomosis. The size of the longitudinal incision in the recipient balloon (side vessel) was more than one and a half times the caliber of the balloon, and the end of the balloon to be anastomosed was cut at an angle of 30 to 45 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] This being so, a number of alternative models have been developed for teaching and development of vascular anastomosis skills, employing a variety of materials ranging from the synthetic, such as rubber and silicone gloves, to vegetable produce. 13,14 One such model, which was used in this study, was created using latex balloons 15 and offers the advantages of low cost, simple construction, the possibility of reuse, and similar diameter and consistency to vascular structures typically involved in procedures in vivo, such as brachiocephalic fistulas and femoropopliteal bypass.…”
Section: Introductionmentioning
confidence: 99%